Toward an informed usage of online resources and collaboration tools for a better educational environment. (18th December 2017) - Ibrahim, Magdy M.
Abstract: Recent development in digital technologies not only enabled us to address many issues in architectural education but created new complexities as well. In this case, the availability of online resources has created an educational and moral paradox. Resources that are useful to professionals might not be as helpful to students who are supposed to draft the most mundane elements of their work themselves. However, students do have access to the same resources professional have. The natural evolution of today's social networks and the plethora of online websites that offer ready-made, well drafted architectural solutions has also greatly enforced the movement. For instance, Facebook groups have become a significant source of support for beginners in many fields with questionable quality because of the unknown level of knowledge of the active group members. From an educational standpoint, student users might treat that content as natural go-to locations to obtain solutions. How much of such behavior is considered plagiarism? This paper investigates the use of online resources habits of the students in educational environments. The purpose of the study is to understand the students' online behavior and the extent that the new medium benefits or hurts their learning. Abstract : The natural evolution of today's social networks and the plethora of online websites that offer ready-made, well drafted architectural solutions have created an educational and moral paradox. The quality of knowledge provided is highly questionable. From an educational standpoint, student users might treat those content websites as natural go-to locations to obtain ready solutions. How much of such behavior is considered plagiarism? How can we regulate the online interaction without scientific authority? This paper investigates the use of online resources habits of the students in educational environments. The purpose of the study is to understand the students' online behavior and the extent that the new medium benefits or hurts their learning.